Spontaneous head movements characterize losing athletes during competition - Drewes, V.; Neumann, N.; Konstantinidis, I.; Helmich, I. (International Journal of Sports Science & Coaching, 2020)
Nonverbal movement behavior and emotions are closely linked processes; however, there is insufficient information about the spontaneous nonverbal expressions in response to experiencing positive and negative emotion, i.e., when winning or losing during sport competitions. Previous research showed that experienced tennis athletes detected losing behavior in athletes more accurately than winning behavior. However, it remained unclear what kind of nonverbal movements characterized losers because the actual movements have not been identified yet. Further research showed that head shaking occurred as an expression of doubt whereas head nodding appeared during successful actions. We therefore hypothesized that losing athletes nonverbally move more, and particularly execute more headshakes when compared to winners. The entire spontaneous nonverbal head movement behavior of professional tennis athletes was video-taped between points during competition and analyzed by two trained and certified raters using a standardized analysis system for nonverbal behavior in relation to won or lost points. The results showed that losers moved their head significantly more often, particularly executing more phasic upward, repetitive sideward (head shaking), and phasic sideward head movements when compared to winning athletes. The present results provide evidence that spontaneous nonverbal head movements differentiate winners from losers during competition. Losing a point in tennis is associated with to increased spontaneous head movement behavior, particularly in upward and sideward directions. Thus, we conclude that professional tennis athletes cannot inhibit their implicit nonverbal expressions that are related to negative emotions when losing.